Catalytic reforming of lignite pyrolysis volatiles over sulfated HZSM-5: Significance of the introduced extra-framework Al species. (1st August 2020) - Zhao, Jing-Ping; Cao, Jing-Pei; Wei, Fu; Feng, Xiao-Bo; Yao, Nai-Yu; Zhao, Yun-Peng; Zhao, Ming; Zhao, Xiao-Yan; Zhang, Jian-Li; Wei, Xian-Yong
Graphical abstract: Highlights: Sulfated HZSM-5 zeolite was prepared by dealumination, realumination and sulfation. The introduced extra-framework Al affected the textural-acid properties of catalysts. Sulfation of catalyst after re-introduced extra-framework Al enhanced LAs production. The highest LAs and lowest coke yield were produced over SO4 2− /DHZ5-A. Abstract: Sulfated HZSM-5 zeolite prepared by dealumination, realumination and sulfation was used as the active mesoporous materials to promote the formation of light aromatics during catalytic reforming of volatiles from Shengli lignite pyrolysis. The results show that HCl-dealumination significantly increased the total pore volume (especially mesopores) and average pore size while reducing acid strength and amount of acid sites. The incorporation of the extra-framework Al species to HZSM-5 combined with SO4 2− to form superacidic surface sulfate complex exhibited an increase in the yield of light aromatics and a decrease in the yield of coke in comparison with that of original HZSM-5. Among the modified catalysts, SO4 2− /DHZ5-A (introduced the calcined Al2 O3 after HCl-dealumination and modified with (NH4 )2 SO4 ) with the acidity enhancement by sulfation obtained the maximum light aromatics yield of 27.3 mg/g and the lowest coke yield of 2.7%. The relationship between the physic-chemical properties of catalysts and the product distribution was proposed to understand the formation of light aromatics.